The state as guarantor of the victims' right to the truth in Colombia - Petro González, Ingrid Regina Petro González; Naranjo Tabares, Daniela; Petro González, Ingrid Regina; Naranjo Tabares, Daniela; Petro González, Ingrid Regina; Naranjo Tabares, Daniela (Corporación Universitaria Americana, 2020)
The victim’s right to the truth has had a wide recognition in the international framework of human rights, not just by jurisprudential via but also doctrinal. Inquire in the State’s rol as a guarantor of the right to the truth of the Colombian conflict victims during the peace process, takes validity for of the compliments of the rules that integrate the constitutional side and for the politic will and legislative state of establishing the model of transitional justice.